Adsorption of carbon dioxide using activated carbon impregnated with Cu promoted by zinc - Hosseini, Soraya; Bayesti, Iman; Marahel, Ehsan; Babadi, Farahnaz Eghbali; Abdullah, Luqman Chuah; Choong, Thomas Shean Yaw (Elsevier, 2015)
In the present study, modified activated carbon (AC) was used in a fixed-bed column for CO2 adsorption of gaseous mixtures. The adsorbents were prepared by impregnation two metals Cu and Zn on the surface of the acid modified AC using a two-stage modification. At the first stage, the samples of AC were pretreated by oxidizing agent (nitric acid) to increase the amount of oxygen surface groups and at the second stage, the acid modified AC were impregnated by two metal salts Cu and Zn on the surface to produce a superior CO2 adsorbent. Metal-loaded acid modified AC was prepared by using different ratios of Cu/Zn ranging from 4 to 20%. The CO2 adsorbed have been measured over the temperature range of (30–50 °C), pressure (100–200 kPa) and CO2 concentrations from 5 to 50%. An increase of 49% CO2 adsorbed was resulted by using modified activated carbon. The breakthrough curves indicated that the breakthrough time increased with increasing the operating pressure, and decreased with increasing the temperature from 30 to 50 °C and CO2 concentration from 5 to 50%. The deactivation model was successfully applied to analyze the breakthrough curves under various operating conditions.